Analysis of Religious Values in the Cow Birthday Tradition - Saeful Anwar; Yogi Prana Izza; Arif Fatikhur Ridho; Suttrisno Suttrisno; Mohammad Anas Bin Ali (Journal Evaluation in Education (JEE), 2025)
Purpose of the study: The rapid advancement of technology has influenced village communities, leading to a gradual loss of identity and neglect of local culture, customs, and wisdom, as foreign cultures become more favored. This study aims to explore the procession and religious values embedded in the cow birthday tradition in Tegalagung Village, Semanding District, Tuban Regency. Methodology: This research employs a descriptive qualitative approach. The sample is selected using purposive sampling, involving respondents such as religious leaders, community figures, and Tegalagung village officials. Data collection methods include interviews, observations, and documentation. Data analysis involves data reduction, data display, and drawing conclusions. Main Findings: The cow birthday tradition involves a series of activities starting with the preparation of ketupat (rice cakes wrapped in palm leaves or janur). Neighbors gather at the cowshed, followed by a communal prayer. The cow is then decorated with ketupat sungu and ketupat kepal, and the ketupat is distributed. Novelty/Originality of the Study: This study offers a unique perspective by examining the intersection of indigenous traditions and religious values. It highlights how rural communities maintain religious awareness through cultural practices. The findings suggest that preserving such traditions, in harmony with modern religious understanding, can strengthen community bonds and spiritual consciousness. Future research may explore similar traditions in different cultural settings.